PENGARUH EKSTRAK KAYU ULIN (Eusideroxylon zwageri) TERHADAP SERANGAN RAYAP KAYU KERING (Cryptotermes cynocephalus Light): PENELITIAN PENDAHULUAN - Mohammad Listianto Raharjo; Desi Mustika Amaliyah; Ratri Yuli Lestari; Budi Tri Cahyana (Jurnal Penelitian Hasil Hutan, 2020)
Dry wood termites attack is one of the problems that cause huge losses in timber construction. One way to solve thisproblem is by preserving wood, with synthetic chemicals or natural ingredients. The purpose of this preliminary researchwas to determine the effect of ironwood powder extract as a natural wood preservative. Preservation methods conductedwere cold immersion at normal temperature (± 25°C) and hot immersion at 80°C. Variations in the concentrationare 5%, 10%, 15%, and 20%. Variation of immersion time are 1, 2, and 3 days for the cold immersion and 0.5; 1;2; 3 hours for the hot immersion. Results show that mortality data and the degree of attack of dry wood termites. Theresults showed that the mortality of the dry wood termites increased 4−6%. However, no difference was found on thedegree of attacks between preserved and control wood.